2015
DOI: 10.1002/jbm.b.33561
|View full text |Cite
|
Sign up to set email alerts
|

Bone regeneration in critical bone defects using three‐dimensionally printed β‐tricalcium phosphate/hydroxyapatite scaffolds is enhanced by coating scaffolds with either dipyridamole or BMP‐2

Abstract: Bone defects resulting from trauma or infection need timely and effective treatments to restore damaged bone. Using specialized three-dimensional (3-D) printing technology we have created custom 3-D scaffolds of hydroxyapatite (HA)/Beta-Tri-Calcium Phosphate (β-TCP) to promote bone repair. To further enhance bone regeneration we have coated the scaffolds with dipyridamole, an agent that increases local adenosine levels by blocking cellular uptake of adenosine. 15% HA:85% β-TCP scaffolds were designed using Rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 42 publications
3
123
0
Order By: Relevance
“…Though highly osteoconductive, the majority of the scaffolds alone are not thought to be particularly osteoinductive, which limits their applicability in the reconstruction of large bone defects . Therefore, recent studies have investigated the combination of 3D printed scaffolds with an added osteoinductive agent such as rhBMP‐2 …”
Section: Discussionmentioning
confidence: 99%
“…Though highly osteoconductive, the majority of the scaffolds alone are not thought to be particularly osteoinductive, which limits their applicability in the reconstruction of large bone defects . Therefore, recent studies have investigated the combination of 3D printed scaffolds with an added osteoinductive agent such as rhBMP‐2 …”
Section: Discussionmentioning
confidence: 99%
“…Several materials have been developed and analyzed to be used for this purpose, including bioactive ceramics such as hydroxyapatite (HA) [5], beta-tricalcium phosphate (b-TCP) [6], biphasic calcium phosphate (BCP) [7], calcium phosphate 2 International Journal of Polymer Science cements [8], bioactive glass [9], and several biodegradable polymers [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Microneedle, tapered tip, or nozzle based syringe extrusion methods were widely applied in the reported extrusion-based bioprinting approaches7124344. We herein found that the micropipette-based extrusion method is a good approach to print tightly packed PLGA microspheres.…”
Section: Discussionmentioning
confidence: 80%
“…3D printing of scaffolds345 have been demonstrated by using bio-inert materials of metals6, ceramics7, polymers8, hydrogels9 and even smart materials10. 3D bioprinting is the layer-by-layer spatial patterning and assembling of living cells together with biologics and/or biomaterials with a prescribed organization, forming a 3D living cellular construct2311.…”
mentioning
confidence: 99%